Cultura y turismo comunitario en la parroquia Cubijíes, cantón Riobamba - Herrera Sinailin, José Roberto (2021)
ABSTRACT The research entitled "Culture and Community Tourism in the Cubijíes parish, in Riobamba canton" has generated its interest in community tourism mainly, so the lack of adequate management and knowledge of community tourism has proposed finding an alternative solution through documentary research, descriptive and methods, taking into account the transectional non-experimental design, to be able to understand the behavior of their variables in a determined period of time based on the art that they count on the type of culture if it is the adapted one to be able to be implemented like an attractiveness and the ancestral knowledge putting in practice the values and the customs, creating new opportunities of internal development on the part of the Cubijíes community. We visited Cubijies community to know if it has the basic complementary tourist services to offer a better service, by means of the analysis of documents, magazines, press articles, papers, A solution can be reached by identifying the needs that the population has to improve the quality of life and the improvement of community tourism, and the conclusion is the Cubijíes characteristics have can be used for the implementation of new methods to improve positively currently , in the social-cultural and economic aspects, recommending the local people to get involved in a direct way and to have a greater commitment, being supported by the different tourist and government entities which can help with an adequate guidelines instruction to be fulfilled to progress in the strengthening of tourism, guiding us in the strategies we could achieve in a SWOT analysis. Keywords: Culture, community tourism, cultural heritage, tourist services, Cubijíes. Reviewed by: Mgs. Janneth Caisaguano Villa. ENGLISH PROFESSOR c.c. 0602305443